Dynamics of the Development of Turkish-Chinese Relations: the Impact of the Chinese Factor on South Caucasus - Khojayan, Karine (YSU Journal of International Affairs, 2021)
Despite a number of unresolved and sensitive political issues, the economic relationship between Turkey and the People’s Republic of China is constantly developing. Turkey has already become a critical hub for the Chinese “Belt and Road” initiative. Chinese capital is increasing in the Turkish economy, pushing back a number of problematic issues. In the meantime, China’s role is growing in the South Caucasus region, making the countries revise and reformulate their foreign policy agenda in line with international and regional processes.